Two-component heat-conducting gel with high elongation and high rebound resilience and preparation method of two-component heat-conducting gel
By using a two-component thermal conductivity gel with high elongation and high resilience in the thermal interface material, a fishing net/sponge-like structure is formed by using cyclic vinyl silicone oil and hydrogen silicone addition reaction, and thermal filler is added, the problems of dropping and interface separation of the thermal interface material under vibration and displacement are solved, achieving efficient thermal conductivity and long-term stable use effect.
Patent Information
- Application Number
- CN202411785642.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-20
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
Existing thermal interface materials are prone to falling, tearing, and interface separation when the vehicle is vibrating and displacement, resulting in an increase in the interface thermal resistance and a decrease in thermal conductivity, affecting the heat dissipation effect of electronic components.
A two-component thermal conductivity gel with high elongation and high resilience is used to form a three-dimensional crosslinked fishnet/sponge-like structure through the addition reaction of cyclic vinyl silicone oil and hydrogen silicone, and a thermal filler is added to improve thermal conductivity and mechanical properties.
It realizes the long-term effective thermal conductivity under vibration and displacement environments, avoids the drop of thermal interface materials and interface separation, and ensures the stable working and service life of electronic components.
Smart Images

Figure BDA0005173967670000021 
Figure BDA0005173967670000031 
Figure BDA0005173967670000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal conductive interface materials, and in particular relates to a two-component thermal conductive gel with high elongation and high resilience and a preparation method thereof. Background Art
[0002] With the popularity of new energy vehicles and autonomous driving, vehicles have more and more functions. In order to cope with various complex environments, the computing power of electronic components such as on-board chips has been greatly improved. With the continuous improvement of chip performance and the increasing integration of vehicle controllers, the heat generated by their operation is also increasing, resulting in higher operating temperatures. If the heat cannot be dissipated in time, the working performance and service life of electronic components such as chips will be greatly reduced, resulting in the inability to quickly handle sudden problems during vehicle driving, which will pose a great safety hazard to vehicle travel.
[0003] As vehicles are driving, they will inevitably encounter various complex road conditions, which will cause severe vibration of the vehicle body, deformation of the entire vehicle, etc., and more or less displacement will inevitably occur between the vehicle electronic components and the heat sink. If the thermal interface material used between the vehicle electronic components and the heat sink cannot adapt to this displacement, it will cause the thermal interface material to fall off, tear, and separate from the interface, resulting in an increase in the thermal resistance of the interface between the vehicle electronic components and the heat sink, a deterioration in the heat dissipation effect, an increase in temperature, and the burning of the chip. Summary of the invention
[0004] In view of the above-mentioned prior art, the present invention provides a two-component thermally conductive gel with high elongation and high resilience and a preparation method thereof. The specific technical scheme is as follows:
[0005] The first object of the present invention is to provide a two-component thermally conductive gel with high elongation and high resilience, comprising the following components in parts by weight:
[0006] Component A:
[0007] 3-8 parts of cyclic vinyl silicone oil; 0.2-0.8 parts of coupling agent, 0.1-0.5 parts of catalyst; 50-60 parts of large-size spherical aluminum nitride, 15-25 parts of small-size spherical aluminum nitride, 15-25 parts of zinc oxide;
[0008] Component B:
[0009] 2-5 parts of cyclic vinyl silicone oil; 0.5-3 parts of cyclic hydrogen-containing silicone oil; 1-4 parts of double-ended hydrogen-containing silicone oil; 0.2-0.8 parts of coupling agent, 0.1-0.5 parts of inhibitor; 50-60 parts of large-particle spherical aluminum nitride, 15-25 parts of small-particle spherical aluminum nitride, and 15-25 parts of zinc oxide.
[0010] The present invention observes the high tensile and high compression resilience of porous materials such as fishing nets and sponges in life, and uses the ring-shaped silicone oil and the hydrosilylation reaction plus the elasticity of the silicone oil molecular chain itself to achieve three-dimensional cross-linking and weave into a molecular-sized fishing net / sponge structure; then add a suitable proportion of thermal conductive fillers to achieve high thermal conductivity, high elongation, and high resilience. The high thermal conductivity of the two-component thermal conductive gel of the present invention can conduct the heat generated by electronic components in time to ensure the working stability of the printed circuit board (PCB); its high elongation and high resilience can effectively solve the problem of increased interface thermal resistance and decreased thermal conductivity after delamination caused by stress changes in a vibration environment.
[0011] Furthermore, the structure of the cyclic vinyl silicone oil is shown in formula (1):
[0012]
[0013] Furthermore, the structure of the cyclic hydrogen-containing silicone oil is shown in formula (2):
[0014]
[0015] Furthermore, the viscosity of the cyclic vinyl silicone oil is 50 to 1000 mPa·s, more preferably 50 to 300 mPa·s, and more preferably 100 mPa·s; the vinyl content of the cyclic vinyl silicone oil is 0.1 to 0.8 mmol / g, more preferably 0.2 to 0.5 mmol / g, and more preferably 0.4 mmol / g.
[0016] Furthermore, the viscosity of the cyclic hydrogen-containing silicone oil is 20 to 300 mPa·s, more preferably 50 to 100 mPa·s, and more preferably 80 mPa·s; the hydrogen content of the cyclic hydrogen-containing silicone oil is 0.1 to 1.0 mmol / g, more preferably 0.3 to 0.6 mmol / g, and more preferably 0.5 mmol / g.
[0017] Furthermore, the cyclic vinyl silicone oil and the cyclic hydrogen-containing silicone oil are separated by gel permeation chromatography or thin film evaporator.
[0018] Due to the equilibrium reaction of silicone oil synthesis, the oil has linear structure and ring structure. The present invention uses gel permeation chromatography (GPC) or thin film evaporator to separate the ring structure in the silicone oil, and combines it with hydrosilylation to weave into a three-dimensional network structure, which greatly improves the elongation and resilience of the two-component thermal conductive gel.
[0019] Furthermore, the cyclic vinyl silicone oil separation method is as follows: the vinyl silicone oil synthesized by base catalysis is matched with a gel chromatography column with a pore size of 10um, and the cyclic vinyl silicone oil with a viscosity of 50 to 150 mPa·s is separated and collected by utilizing the characteristics that small molecules pass quickly and large molecules pass slowly.
[0020] Furthermore, the cyclic vinyl silicone oil with a viscosity of 50 to 150 mPa·s is matched with a gel chromatography column with a pore size of 2 to 5 um, and the cyclic vinyl silicone oil with a viscosity of 100 to 120 mPa·s is accurately separated and collected by utilizing the characteristics that the linear body passes quickly and the cyclic body passes slowly.
[0021] Furthermore, the cyclic hydrogenated silicone oil separation method is as follows: the hydrogenated silicone oil synthesized by acid catalysis is matched with a gel chromatography column with a pore size of 10 um, and the cyclic hydrogenated silicone oil with a viscosity of 50 to 150 mPa·s is initially separated and collected by taking advantage of the characteristics that small molecules pass quickly and large molecules pass slowly.
[0022] Furthermore, the cyclic hydrogenated silicone oil with a viscosity of 50 to 150 mPa·s is matched with a gel chromatography column with a pore size of 2 to 5 um, and the characteristics of fast passage of linear bodies and slow passage of cyclic bodies are utilized to accurately separate and collect the hydrogenated silicone oil with a viscosity of 80 to 100 mPa·s.
[0023] Furthermore, the viscosity of the double-ended hydrogen-containing silicone oil is 50 to 500 mPa·s, more preferably 100 to 300 mPa·s, and more preferably 200 mPa·s; the hydrogen content of the double-ended hydrogen-containing silicone oil is 0.1 to 1.0 mmol / g, more preferably 0.2 to 0.8 mmol / g, and more preferably 0.3 mmol / g.
[0024] Furthermore, the catalyst is a platinum catalyst, the inhibitor is alkynyl cyclohexanol, and the coupling agent is dodecyltrimethoxysilane.
[0025] Furthermore, the large-particle-size spherical aluminum nitride powder has a particle size of 20 to 90 μm, preferably 30 to 70 μm, and more preferably 50 μm.
[0026] Furthermore, the small-particle-size spherical aluminum nitride powder has a particle size of 1 to 10 μm, more preferably 2 to 5 μm, and more preferably 3 μm.
[0027] Furthermore, the particle size of the zinc oxide is 0.5 to 10 μm, more preferably 0.8 to 5 μm, and even more preferably 4 μm.
[0028] The second object of the present invention is to provide a method for preparing the above-mentioned two-component thermally conductive gel with high elongation and high resilience, comprising the following steps:
[0029] 1) Add cyclic vinyl silicone oil, coupling agent, catalyst, large-size spherical aluminum nitride, small-size spherical aluminum nitride and zinc oxide to a planetary gravity dispersion device, stir for 1 to 5 minutes at a speed of 800 to 1000 rpm and a vacuum degree of less than -0.09 MPa to evenly disperse component A; add cyclic vinyl silicone oil, cyclic hydrogen-containing silicone oil, double-end hydrogen-containing silicone oil, coupling agent, large-size spherical aluminum nitride, small-size spherical aluminum nitride and zinc oxide to a planetary gravity dispersion device; stir for 1 to 5 minutes at a speed of 800 to 1000 rpm and a vacuum degree of less than -0.09 MPa to evenly disperse component B;
[0030] 2) Pour the dispersed A and B components into a planetary stirring kettle respectively, stir for 40 to 80 minutes at a temperature of 60 to 100° C., a rotation speed of 20 to 60 rpm, and a vacuum degree of less than -0.09 MPa; continue to heat to 100 to 150° C., stir for 80 to 100 minutes at a rotation speed of 20 to 60 rpm and a vacuum degree of less than -0.09 MPa;
[0031] 3) After component A is cooled to room temperature, remove from the pot and pack; after component B is cooled to room temperature, add the inhibitor, stir evenly, remove from the pot and pack.
[0032] The beneficial effects of the present invention are:
[0033] The present invention utilizes the annular silicone oil and the hydrosilylation reaction as well as the elasticity of the silicone oil molecular chain itself to achieve three-dimensional cross-linking and weave a molecular-sized fishing net / sponge-like structure; a suitable proportion of thermal conductive fillers is added to achieve high thermal conductivity, high elongation, and high resilience, and is applied to heating interfaces that are prone to vibration and displacement, and can maintain long-term effective stability of use. DETAILED DESCRIPTION
[0034] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0035] Separation of cyclic vinyl silicone oil:
[0036] (1) Select commercially available vinyl silicone oil synthesized by base catalysis (Zhejiang Runhe Silicone New Material Co., Ltd., model Vi-321), match it with a gel chromatography column with a pore size of 10 μm, and use the characteristics of small molecules passing quickly and large molecules passing slowly to separate and collect cyclic vinyl silicone oil with a viscosity of 50 to 150 mPa·s;
[0037] (2) Using a gel chromatography column with a pore size of 2 to 5 μm, the linear phase passes quickly while the annular phase passes slowly, and the annular vinyl silicone oil with a viscosity of 100 to 120 mPa·s is accurately separated and collected.
[0038] Separation of cyclic hydrogenated silicone oil:
[0039] (1) A commercially available acid-catalyzed hydrogenated silicone oil (model RH-H33 from Zhejiang Runhe Organic Silicone New Materials Co., Ltd.) was selected and matched with a 10 μm pore size gel chromatography column. The characteristics of small molecules passing through quickly and large molecules passing through slowly were utilized to preliminarily separate and collect the cyclic hydrogenated silicone oil with a viscosity of 50 to 150 mPa·s;
[0040] (2) Using a gel chromatography column with a pore size of 2 to 5 μm, the linear phase passes quickly while the annular phase passes slowly, and the hydrogenated silicone oil with a viscosity of 80 to 100 mPa·s is accurately separated and collected.
[0041] The cyclic vinyl silicone oil used in the following examples or comparative examples has a viscosity of 100 mPa·s and a vinyl content of 0.4 mmol / g; the cyclic hydrogenated silicone oil has a viscosity of 80 mPa·s and a hydrogen content of 0.5 mmol / g; the double-ended hydrogenated silicone oil has a viscosity of 200 mPa·s and a hydrogen content of 0.3 mmol / g; the catalyst is a platinum catalyst; the inhibitor is alkynyl cyclohexanol; the coupling agent is dodecyltrimethoxysilane; the large-particle spherical aluminum nitride powder is a spherical aluminum nitride powder with a particle size of 50 μm; the small-particle spherical aluminum nitride powder is a spherical aluminum nitride powder with a particle size of 3 μm; and the particle size of zinc oxide is 4 μm.
[0042] Example:
[0043] A preparation method of a two-component thermally conductive gel with high elongation and high resilience comprises the following steps:
[0044] 1) Add 5.4 parts of cyclic vinyl silicone oil, 0.5 parts of coupling agent, 0.1 parts of catalyst, 57.0 parts of large-particle spherical aluminum nitride, 21.0 parts of small-particle spherical aluminum nitride and 16.0 parts of zinc oxide into a planetary gravity dispersion device, stir for 2 minutes at a speed of 900 rpm and a vacuum degree of less than -0.09 MPa to evenly disperse component A;
[0045] 2) Add 2.4 parts of cyclic vinyl silicone oil, 1.0 parts of cyclic hydrogenated silicone oil, 2.0 parts of double-terminal hydrogenated silicone oil, 0.5 parts of coupling agent, 57.0 large-particle spherical aluminum nitride, 21.0 small-particle spherical aluminum nitride and 16.0 zinc oxide to a planetary gravity dispersion device; stir for 2 minutes at a speed of 900 rpm and a vacuum degree of less than -0.09 MPa to evenly disperse component B;
[0046] 3) Pour the evenly dispersed component A into a planetary stirring kettle, stir for 80 minutes at a temperature of 80°C, a rotation speed of 40 rpm, and a vacuum degree of less than -0.09 MPa; continue to heat to 125°C, stir for 90 minutes at a rotation speed of 40 rpm and a vacuum degree of less than -0.09 MPa; cool component A to room temperature, remove from the kettle, and load;
[0047] 4) Pour the evenly dispersed component B into a planetary stirring kettle, stir for 80 minutes at a temperature of 80°C, a rotation speed of 40 rpm, and a vacuum degree of less than -0.09 MPa; continue to heat to 125°C, stir for 90 minutes at a rotation speed of 40 rpm and a vacuum degree of less than -0.09 MPa; after component B is cooled to room temperature, add 0.1 parts of inhibitor, stir evenly, remove from the pot, and load.
[0048] Comparative Example:
[0049] A preparation method of a two-component thermally conductive gel comprises the following steps:
[0050] 1) Add 5.4 parts of linear vinyl silicone oil (HV-100, Zhejiang Chuanhe Chemical Co., Ltd.), 0.5 parts of coupling agent, 0.1 parts of catalyst, 57.0 parts of large-particle spherical aluminum nitride, 21.0 parts of small-particle spherical aluminum nitride and 16.0 parts of zinc oxide to a planetary gravity dispersion device, stir for 2 minutes at a speed of 900 rpm and a vacuum degree of less than -0.09 MPa to evenly disperse component A;
[0051] 2) Add 2.4 parts by weight of linear vinyl silicone oil (HV-100, Zhejiang Chuanhe Chemical Co., Ltd.), 1.0 parts of linear hydrogenated silicone oil (SH-18, Zhejiang Chuanhe Chemical Co., Ltd.), 2.0 parts of double-terminal hydrogenated silicone oil, 0.5 parts of coupling agent, 57.0 large-particle spherical aluminum nitride, 21.0 small-particle spherical aluminum nitride and 16.0 zinc oxide to a planetary gravity dispersion device; stir for 2 minutes at a speed of 900 rpm and a vacuum degree of less than -0.09 MPa to evenly disperse component B;
[0052] 3) Pour the evenly dispersed component A into a planetary stirring kettle, stir for 80 minutes at a temperature of 80°C, a rotation speed of 40 rpm, and a vacuum degree of less than -0.09 MPa; continue to heat to 125°C, stir for 90 minutes at a rotation speed of 40 rpm and a vacuum degree of less than -0.09 MPa; cool component A to room temperature, remove from the kettle, and load;
[0053] 4) Pour the evenly dispersed component B into a planetary stirring kettle, stir for 80 minutes at a temperature of 80°C, a rotation speed of 40 rpm, and a vacuum degree of less than -0.09 MPa; continue to heat to 125°C, stir for 90 minutes at a rotation speed of 40 rpm and a vacuum degree of less than -0.09 MPa; after component B is cooled to room temperature, add 0.1 parts of inhibitor, stir evenly, remove from the pot, and load.
[0054] The performance of the two-component thermally conductive gels obtained in the examples and comparative examples was tested, and the results are shown in Table 1.
[0055] ① Thermal conductivity:
[0056] Test equipment: hot disk, test standard: ISO 22007-2;
[0057] ② Thermal resistance:
[0058] Test equipment: Ruiling thermal resistance meter, test standard: ASTM D5470;
[0059] ③Hardness:
[0060] Test equipment: shore OO hardness tester, test standard: ASTM D2240;
[0061] ④Tensile strength:
[0062] Testing equipment: universal material testing machine, testing standard: GB / T 1040.1-2018;
[0063] ⑤ Elongation at break:
[0064] Testing equipment: universal material testing machine, testing standard: GB / T 1040.1-2018;
[0065] ⑥Rebound rate after compression 50% + 24h:
[0066] 1. Mix components A and B in a ratio of 1:1, roll into 3mm, and cure at 125℃ for 30min;
[0067] 2. Use 1in 2 Use a circular cutter to cut out a disc and measure the thickness h1;
[0068] 3. Clamp the disc between two 4mm thick glass plates, add a feeler gauge of h1 / 2 thickness around the disc, and press the glass with a G-shaped clamp;
[0069] 4. Release the G-clamp after 24 hours of rest, and test the thickness h2 after 2 hours of rest;
[0070] 5. Calculate the rebound rate = (h2 / h1)*100%.
[0071] Table 1 Performance test results of the two-component thermally conductive gel obtained in the examples and comparative examples
[0072]
[0073] It can be seen from the test data in Table 1 that after the A and B components of the two-component thermally conductive gel of the embodiment and the comparative example are mixed and cured in a ratio of 1:1, the elongation of the two-component thermally conductive gel of the embodiment is significantly higher than that of the two-component thermally conductive gel of the comparative example with a linear structure component; after the cured sheet is compressed by 50% for 24 hours, the two-component thermally conductive gel of the embodiment can rebound to 90% of the original thickness, which is significantly greater than 60% of the two-component thermally conductive gel of the comparative example with a linear structure component. The two-component thermally conductive gel of the components of the present invention has obvious advantages in high elongation and high resilience.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A two-component thermally conductive gel with high elongation and high resilience, characterized in that: It comprises the following components in parts by weight: Component A: 3-8 parts of cyclic vinyl silicone oil; 0.2-0.8 parts of coupling agent, 0.1-0.5 parts of catalyst; 50-60 parts of large-size spherical aluminum nitride, 15-25 parts of small-size spherical aluminum nitride, 15-25 parts of zinc oxide; Component B: 2-5 parts of cyclic vinyl silicone oil; 0.5-3 parts of cyclic hydrogen-containing silicone oil; 1-4 parts of double-ended hydrogen-containing silicone oil; 0.2-0.8 parts of coupling agent, 0.1-0.5 parts of inhibitor; 50-60 parts of large-particle spherical aluminum nitride, 15-25 parts of small-particle spherical aluminum nitride, and 15-25 parts of zinc oxide.
2. The two-component thermally conductive gel with high elongation and high resilience according to claim 1, characterized in that: The structure of the cyclic vinyl silicone oil is shown in formula (1):
3. The two-component thermally conductive gel with high elongation and high resilience according to claim 1, characterized in that: The structure of the cyclic hydrogen-containing silicone oil is shown in formula (2):
4. The two-component thermally conductive gel with high elongation and high resilience according to claim 1, characterized in that: The viscosity of the cyclic vinyl silicone oil is 50 to 1000 mPa·s, and the vinyl content of the cyclic vinyl silicone oil is 0.1 to 0.8 mmol / g.
5. The two-component thermally conductive gel with high elongation and high resilience according to claim 1, characterized in that: The viscosity of the cyclic hydrogen-containing silicone oil is 20 to 300 mPa·s, and the hydrogen content of the cyclic hydrogen-containing silicone oil is 0.1 to 1.0 mmol / g.
6. The two-component thermally conductive gel with high elongation and high resilience according to claim 1, characterized in that: The cyclic vinyl silicone oil and the cyclic hydrogen-containing silicone oil are separated by gel permeation chromatography or thin film evaporator.
7. The two-component thermally conductive gel with high elongation and high resilience according to claim 1, characterized in that: The viscosity of the double-terminal hydrogen-containing silicone oil is 50-500 mPa·s, and the hydrogen content of the double-terminal hydrogen-containing silicone oil is 0.1-1.0 mmol / g.
8. The two-component thermally conductive gel with high elongation and high resilience according to claim 1, characterized in that: The catalyst is a platinum catalyst, the inhibitor is alkynyl cyclohexanol, and the coupling agent is dodecyltrimethoxysilane.
9. The two-component thermally conductive gel with high elongation and high resilience according to claim 1, characterized in that: The large-diameter spherical aluminum nitride powder has a particle size of 20 to 90 μm, the small-diameter spherical aluminum nitride powder has a particle size of 1 to 10 μm, and the zinc oxide has a particle size of 0.5 to 10 μm.
10. A method for preparing a two-component thermally conductive gel with high elongation and high resilience as claimed in any one of claims 1 to 9, characterized in that: The steps include: 1) Add cyclic vinyl silicone oil, coupling agent, catalyst, large-size spherical aluminum nitride, small-size spherical aluminum nitride and zinc oxide to a planetary gravity dispersion device, stir for 1 to 5 minutes at a speed of 800 to 1000 rpm and a vacuum degree of less than -0.09 MPa to evenly disperse component A; add cyclic vinyl silicone oil, cyclic hydrogen-containing silicone oil, double-end hydrogen-containing silicone oil, coupling agent, large-size spherical aluminum nitride, small-size spherical aluminum nitride and zinc oxide to a planetary gravity dispersion device; stir for 1 to 5 minutes at a speed of 800 to 1000 rpm and a vacuum degree of less than -0.09 MPa to evenly disperse component B; 2) Pour the dispersed A and B components into a planetary stirring kettle respectively, stir for 40 to 80 minutes at a temperature of 60 to 100° C., a rotation speed of 20 to 60 rpm, and a vacuum degree of less than -0.09 MPa; continue to heat to 100 to 150° C., stir for 80 to 100 minutes at a rotation speed of 20 to 60 rpm and a vacuum degree of less than -0.09 MPa; 3) After component A is cooled to room temperature, remove from the pot and pack; after component B is cooled to room temperature, add the inhibitor, stir evenly, remove from the pot and pack.